Generation of cell lines from embryonic quail retina capable of mature neuronal differentiation - Pollerberg, G. Elizabeth; Kuschel, C.; Zenke, Martin (Journal of neuroscience research, 1995)
The avian embryonic retina is widely used as a model system for cellular and molecular studies on central nervous system neurons. We aimed at the generation of cell lines from the early embryonic quail retina by retroviral oncogene transduction. For this, we made use of the retina organ culture system which exhibits both proliferation, necessary for stable oncogene transduction, and initial neuronal differentiation, a prerequisite for the generation of cell lines with mature neuronal properties. The oncogene myc was chosen ac it is both proliferation-inducing and differentiation-compatible. A chimeric gene, mycER, containing v-myc and the hormone-binding domain of the estrogen receptor, was used for transduction in order to allow for hormone regulation of myc activity. Transduced organ-cultured cells from temporal and nasal retina were passaged into sparse single cell cultures. From these, colonies of rapidly dividing cells were isolated and the progeny expanded as cell lines. The lines contained cells with features of neuroepithelial cells, showing vimentin and A2B5. They also contained spontaneously differentiated neuronal cells showing neurofilament L and N-CAM18O. A subpopulation of the neuronal cells exhibited the morphological characteristics of retinal ganglion cells, i.e., large pear-shaped somata each emitting one long process with a distinct growth cone. In addition, they showed the marker profile of retinal ganglion cells, i.e., expression of Thy-1, G4, DMGRASP, Nr-CAM, neurofilament H, and tau. Neuronal differentiation could be induced by the addition of db cAMP and retinoic acid. The mature neuronal features of the lines open new possibilities to study properties of retinal neurons, including ganglion cells, in a defined and manipulable experimental system. © Wiley-Liss, Inc.